Exploring Gen Z Engagement: Work–Life Balance and Flexibility in Creative Programming Work - Anandita, Sylvia; Gunawan, Asep; Febriyansyah, Hevy (Al-Qalam Institue, 2025)
This study investigates the influence of Work-Life Balance (WLB) and Flexible Work Arrangements (FWA) on Employee Engagement (EE) among Generation Z professionals in Indonesia’s creative programming sector. With Gen Z’s increasing demand for autonomy and meaningful work, the study used a quantitative descriptive-associative method to collect data from 86 respondents via purposive sampling in LinkedIn programming communities in West Java. The analysis included validity and reliability tests, descriptive statistics, and multiple linear regression. Results reveal that WLB significantly enhances employee engagement, highlighting the importance of balance in time, involvement, and satisfaction. However, FWA does not considerably affect engagement, possibly because it is an expected norm among Gen Z, lacking differentiation unless backed by organizational support or meaningful work. The study emphasizes the importance of prioritizing work-life balance for organizations to enhance employee engagement. Managers should offer not only flexible work arrangements but also meaningful work experiences that align with employees' values. Flexibility should be supported by a strong organizational culture and leadership that fosters well-being and purpose, ensuring higher employee engagement and long-term productivity.